Avaliação do potencial energético do biogás gerado em aterros sanitários que atendem diferentes faixas populacionais - Mello, Andriele Rimoldi (2016)
This study aims to evaluate the energy potential of biogas generated in Brazilian landfills that receive municipal solid waste of populations between 100,000 and 20 million inhabitants for generation and sale of electricity. The literature review presents the main concepts related to the subject matter, dealing with energy issues, municipal solid waste and its disposal in landfill, the generation and use of biogas, energy sales coming from biomass, among others. The methodology presents calculation procedures adopted in order to achieve specific objectives. The quantification of the generated biogas was performed according to the model suggested by the IPCC and this information was made other calculations of methane recovery rate, potential for electricity generation cost of electricity generation from landfill biogas and analysis the economic viability of the investment in biogas energy exploitation projects. The organization of these calculations was made by two studies considering the capacity served by landfills and the power available for sale. Study 1 refers to landfills with capacity for between 100,000 and 4,000,000 inhabitants, with power generation up to 5,000 kW and can market the energy generated by means of compensation. The study covers two populations between 5,000,000 and 20,000,000 inhabitants and power from 1,000 kW to 30,000 kW, whose marketing of energy should be made in free trading environments or regulated trading environments. Landfills with power of 1,000 kW and 5,000 kW can market the energy of both forms. The results show great generation of methane for all studied capabilities, higher than in scenarios with higher recovery rate and population served. The energy potential showed better results for cases with greater recovery of methane and conversion efficiency with sufficient quantity to produce energy. The generation cost decreased with increased capacity due to economies of scale, ranging from $ 0.10 per kWh to $ 0.03 kWh. Both studies demonstrate economic viability and attractiveness in all projects from 100 thousand inhabitants, ensuring return on investment in no more than 13 years. Where the marketing of energy can be made either by compensation for the contracting environments, the first alternative was more advantageous, providing a greater return on investment in a shorter period. Finally, the study achieved its objectives with favorable results regarding the use of the potential of biogas from landfills.